Global optimization and complementarity for solving a semi-actuated traffic control problem - M. Lurdes Simões (2011)
The aim of this paper is to find the optimal green split allocation for a queuing system. This system results from a signalized intersection regulated by semi-actuated control in an urban traffic network. The model in question has been formulated as a Mathematical Program with Equilibrium (or Complementarity) Constraints (MPEC). Computational experiments with a sequential complementarity algorithm to attain a global minimum for the MPEC are included to estimate the green times and cycle lengths. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the Organizing Committee.